New Advances in Hydrogenation Processes Fundamentals and Applications - Takht Ravanchi, Maryam (IntechOpen, 2017)
Hydrogen is one of the abundant elements on earth majorly in the form of water (H2O) and mainly as hydrogen gas (H2). Catalytic hydrogenation is a key reaction that has versatile applications in different industries. The main objective of this book is to bring together various applications of hydrogenation through the perspective of leading researchers in the field. This book is intended to be used as a graduate-level text book or as a practical guide for industrial engineers.